2015
DOI: 10.1002/lno.10236
|View full text |Cite
|
Sign up to set email alerts
|

Waterborne copper impairs grazer-induced colony formation and photosynthetic efficiency inScenedesmus obliquus

Abstract: Grazer-induced defense in phytoplankton is known to stabilize community dynamics within aquatic environments. Metal contamination in waters is of grave concern worldwide due to its cytotoxicity to organisms. had no significant effect on algal growth and photosynthesis; however, the ability of S. obliquus to form colonies in response to Daphnia filtrate was impaired. These results suggest high sensitivity of grazer-induced morphological defense to Cu toxicity in Scenedesmus. Metal contamination may result in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 53 publications
(58 reference statements)
0
5
1
Order By: Relevance
“…Inhibited feeding by colonial algal prey can decrease somatic growth and reproduction in Daphnia (Lürling and Van Donk 1996), resulting in reduced population growth. While our findings suggest that SDS indirectly affects Daphnia-Scenedesmaceae systems by promoting colony formation, recent studies have also demonstrated that some pollutants can impair the inducible defense in Scenedesmus against Daphnia grazing cues at harmless concentrations (Huang et al 2016: Zhu et al 2019Zhu et al 2020). Interfered induction of colonies can expose Scenedesmaceae to higher grazing risk, leading to population collapse of the algae.…”
contrasting
confidence: 48%
“…Inhibited feeding by colonial algal prey can decrease somatic growth and reproduction in Daphnia (Lürling and Van Donk 1996), resulting in reduced population growth. While our findings suggest that SDS indirectly affects Daphnia-Scenedesmaceae systems by promoting colony formation, recent studies have also demonstrated that some pollutants can impair the inducible defense in Scenedesmus against Daphnia grazing cues at harmless concentrations (Huang et al 2016: Zhu et al 2019Zhu et al 2020). Interfered induction of colonies can expose Scenedesmaceae to higher grazing risk, leading to population collapse of the algae.…”
contrasting
confidence: 48%
“…obliquus . This phenomenon can increase the risk of predation by herbivores, thereby disrupting the inducible phytoplankton community 17 , 18 . In contrast, they also showed that the morphological defense in S .…”
Section: Introductionmentioning
confidence: 99%
“…The expression of inducible predator‐resistant traits involves a series of complex processes, including the identification of chemical signals and resource allocation (Effertz and von Elert 2014;Bell et al 2019; Gu et al 2020); thus, the type and intensity of expression of these traits and their subsequent effects on the population dynamics of prey can be affected by environmental conditions. Many studies have found that the ability of some aquatic organisms to form induced defense varies with temperature (Zhu et al 2019), food types (Bell et al 2019; Gu et al 2020), availability of nutrients (Zhu et al 2016), CO 2 concentration (Huang et al 2018), UVB radiation stress (Rose et al 2012; Sun et al 2020), light intensity (Effertz and von Elert 2014), pollutants (Pestana et al 2010; Huang et al 2016; Zhu et al 2020), and salinity (Bezirci et al 2012). It is well known that calcium is an important element in signal transduction (Clapham 2007) and can change the material and energy distribution of organisms (Pérez‐Fuentetaja and Goodberry 2016; Huang et al 2020).…”
mentioning
confidence: 99%